Rancang Bangun Mesin Press Serbuk Kayu Pembuatan Papan Partikel Sebagai Sarana Penunjang Kegiatan Praktikum: Design and Construction of a Wood Powder Press Machine For Making Particle Board as a Supporting Means For Practical Activities - SUKMA, DODI; Tahrir, Muhammad; Santosa; Kurniawan, Dedy; Suryadi; Astuti, Soleha; Famela, Vidya (PERENNIAL, 2024)
This research activity studies the design of particle board press machines using iron plate materials and manual labor-based hydraulic presses. This research aims to produce a work tool that can facilitate the continuity of processing sawdust into particle boards so that practical activities can be carried out effectively and efficiently while still paying attention to the values determined in the practicum. The research method is carried out using the study of existing tools and will be made another tool with more straightforward work by analyzing the factors of weakness in existing tools. The working mechanism of the sawdust press machine to be made is manual, using human power, and the sawdust press machine is intended for practical student activities in the laboratory.